Effect of community-based physical exercise interventions carried out in primary helath care on plasma inflammatory biomarkers and cardiorespiratory fitness - Papini, Camila Bosqueiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The study aims to verify the effect of community-based physical exercise interventions carried out in primary health care on plasma inflammatory biomarkers and cardiorespiratory fitness. It was performed a 1year quasi-experimental study with female participants of Physical Exercise Interventions carried out in Health Units in Rio Claro City, Sao Paulo State. Two different protocols were implemented. The Intervention 1 (two, 60 minute sessions/week) was based in the Saude Ativa Rio Claro Program (existing since 2001). The intervention 2 (three, 90 minute sessions/week) was based in the physical activity recommendation. In both interventions, aerobic, resistance muscle and stretching exercises were performed. The variables evaluated were: a) Anthropometric variables (body mass, stature, body mass index, waist and hip circumferences); b) Physical Activity level through pedometer; c) Cardiorespiratory fitness test (incremental ergoespirometric test); d) Inflammatory biomarkers (blood plasmatic dosage). The results are present in 3 articles. In the chapter 1, the results showed that the Intervention 1 was effective in reducing CRP and TNFa; and in maintaining the IL10, IL6 and insulin after 1 year of intervention. In the chapter 4, it was demonstrated that Intervention 2 decreased the LDL and glucose levels and improved the resistance insulin of participants. In chapter 5, the results indicated that participants of Intervention 2 developed a greater exercise tolerance and improved the energy cost during walking. These data suggest that cardiorespiratory fitness was enhanced. Some additional analyses indicated that participants of intervention 1 developed a greater exercise tolerance but they did not improve the energy cost during walking. Both interventions were able to improve health-related variables. The development of ...

O presente projeto tem como objetivo verificar o efeito de programas de exercício físico sobre biomarcadores de inflamação e a capacidade cardiorrespiratória em participantes de programas de exercícios físicos oferecidos em Unidades de Saúde do município de Rio Claro-SP. Para atingir os objetivos propostos foi realizado um estudo quase-experimental com duração de 12 meses, onde a amostra foi composta por mulheres participantes de programas de Intervenção com Exercício Físico em Unidades de Saúde. Foram implementados 2 Programas distintos. A Intervenção 1 foi baseada no Programa Saúde Ativa Rio Claro (já existente no Município desde 2001), composta de 2 sessões semanais de exercício físico com duração de 60 minutos. A intervenção 2 foi fundamentada nas recomendações preconizadas para a prática de atividade física, sendo oferecida 3 sessões semanais com duração de 90 minutos. Em ambas intervenções foram desenvolvidas atividades aeróbias, exercícios de força e flexibilidade. As variáveis avaliadas foram: a) Antropometria (Massa Corporal, Estatura, Cálculo do Índice de Massa Corporal, Circunferência da Cintura e Quadril); b) Pedometria; c) Aptidão Cardiorrespiratória (Teste Ergoespirométrico Incremental na esteira); d) Biomarcadores de Inflamação (Dosagem plasmática do sangue). Os resultados estão apresentados em forma de artigo. No capítulo 3, os resultados demonstram que a Intervenção 1 foi efetiva em reduzir concentrações de PCR e TNFα e manter concentrações de IL10, IL6 e insulina após 12 meses de intervenção. No capítulo 4, foi demonstrado que a Intervenção 2 reduziu concentrações de LDL e glicose e ainda melhorou o quadro de resistência à insulina das participantes. No capítulo 5 os dados indicaram que as participantes desenvolveram uma maior tolerância ao exercício e melhoraram o custo energético dos estágios do teste. Isso sugere que a aptidão cardiorrespiratória foi...
Keywords: Physical education and training; Educação fisica; Exercícios físicos; Marcadores bioquímicos; Aptidão cardiorrespiratória